PENGARUH LIKUIDITAS DAN LEVERAGE TERHADAP NILAI PERUSAHAAN DENGAN PROFITABILITAS SEBAGAI VARIABEL INTERVENING - Reni Febriani (FKIP, Universitas Banten Jaya, 2020)
The value of the company was important because of the high valuation of the community on the company's shares, which would be followed by the high level of prosperity of shareholders. This study aimed to determine the effect of proxied liquidity through Current Asset and leverage proxied through the Debt to Equity Ratio of firm value proxied through Price to Book Value with profitability proxied through Return on Asset as an intervening variable. The study population were 144 manufacturing companies listed on the Indonesia Stock Exchange for the period 2014-2018 with a total of 13 companies taken. The method of data analysis used path analysis by testing mediating variables using the sobel method. The results showed 1) Liquidity had a negative and significant effect on firm value. 2) Leverage had a negative and significant effect on firm value. 3) Liquidity did not affect profitability. 4) Leverage had a negative and significant effect on profitability. 5) Profitability has a positive effect on company value. 6) Profitability did not mediate the effect of liquidity and leverage on firm value.